Pengaruh Overtime, Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT.Nagamas Kurnia Sejahtera - Tambunan, Fransisco Wanviano Daniel; Rukhviyanti, Novi (Fakultas Ekonomi Universitas Samudra, 2024)
The study aims to analyze the relationship between overtime, job training, and employee performance, both partially and simultaneously. 80 respondents were used as a purposive sample who were employees of PT. Nagamas Kurnia Sejahtera. The results showed that partially, overtime was proven to have a significant effect on performance, while job training was not proven to have a significant effect on employee performance. Simultaneously, overtime and training were proven to have a significant impact on employee performance. Thus, the results of this study underline the importance of effective management of overtime hours in supporting the achievement of optimal performance. In other aspects, human resources need to consider more effective strategies in designing training programs that can have a significant impact on employee performance.